National practice patterns for clinical T1N0 Nasopharyngeal Cancer in the elderly: a national cancer data base analysis - Post, Carl M.; Adeberg, Sebastian (Anticancer research, 2018)
Background: The standard of care for T1N0 nasopharyngeal cancer (NPC) is definitive radiation therapy (RT). However, practice patterns in the elderly may not necessarily follow national guidelines. Herein, we investigated national practice patterns for T1N0 NPC. Materials and Methods: The National Cancer Data Base (NCDB) was queried for clinical T1N0 primary NPC cases (2004-2013) in patients ≥70 years old. Patient, tumor, and treatment parameters were extracted. Kaplan-Meier analysis was used to compare overall survival (OS) between patients receiving RT versus those under observation. Logistic regression was used to examine variables associated with receipt of RT. Cox proportional hazards modeling determined variables associated with OS. Landmark analysis of patients surviving 1 year or more was performed to assess survival differences between groups. Results: In total, data of 147 patients were analyzed. RT was delivered to 89 patients (61%), whereas 58 (39%) patients underwent observation. On multivariable analysis, older patients were less likely to receive RT (p=0.003), but there were no differences between groups in terms of Charlson-Deyo comorbidity index. Median and 5-year OS in patients receiving RT versus those under observation were 71 and 33 months, and 59% and 48% (p=0.011), respectively. For patients surviving 1 year or more (n=96), there was a strong trend showing that receipt of RT was associated with better median and 5-year OS. Conclusion: This National Data Base analysis shows that observation is relatively common for T1N0 NPC in the elderly, but is associated with poorer survival.
Gesehen am 08.05.2020